Unique Presentation of Glioblastoma with Acute Onset Symptomatology and Disease Recurrence - ul Haq, Mian Iftikhar; Mushtaq, Allah Bux; Aslam, Huma; Mehmood, Shahid; Khalil, Saqib; Azmat, Syeda Khoula; Rehman, Zia ur (Journal of Neonatal Surgery, 2025)
Background: The most common and dangerous type of primary brain tumor is glioblastoma. Focused neurological abnormalities are common in the brief clinical histories that patients typically bring to the clinic. Objective: Aim was to determine the clinical presentation of glioblastoma and it’s postoperatively outcomes. Methods: This prospective/observational study was conducted at Hayatabad Medical Complex, Peshawar from December 2022 to March 2024. Total 35 patients of both gender were presented after providing informed written consent. The CNS tumor registry was used to gather demographic information as well as data on adverse occurrences. Means and standard deviations were the results of the data analysis. SPSS 23.0 was used to analyze all data. Results: The included cases had mean age 65.9 years. 22 (62.9%) cases were males and 13 (37.1%) were females. Post-operatively psychiatric/neurological adverse events were observed early as compared to cardiovascular/respiratory and general adverse events. Frequency of seizure was 25 (71.4%) among all cases. Conclusion: The adverse events that patients with glioblastoma experience are categorized as follows: psychiatric/neurological, cardiovascular/respiratory, and general. At least one seizure will be experienced by the majority of patients.